Stimulation of human osteoblast cells (MG63) proliferation using decanoic acid and isopropyl amine fractions of Wattakaka volubilis leaves. (15th August 2017) - Venugopal, Elakkiya; Ramadoss, Govindarajan; Krishnan, Kannan; Eranezhath, Sujith Subash; Bhattacharyya, Amitava; Rajendran, Selvakumar
Abstract: Objectives: This study was carried out to investigate the impact of various isolated phytochemical components present in the Wattakaka volubilis leaves for the growth and proliferation of human osteoblast like cells (MG63). Key findings: Ethyl acetate was found to be the best solvent for potential extraction of phytocompounds. Further, the MTT assay was carried out to deduce the viability of 44 isolated phytochemicals. Ten phytochemical fractions found to increase the cell growth were subjected to statistical tool namely Plackett–Burman and Central composite design to screen the optimum phytochemical fraction and its dosage. The active phytochemical constituents were analysed and identified as hexadeconoic acid, octadeconoic acid, N, N-diisopropyl(2, 2, 3, 3, 3-pentafluoropropyl)amine using GC-MS and HPLC techniques. The impact of optimized concentration was assessed on osteoblast cells. The maximum % cell viability, % DNA and collagen content were found to be 164.44, 159.32 and 3.81, respectively. Conclusions: The results confirmed that the optimized fraction containing decanoic acid and isopropyl amine at particular concentration stimulated the proliferation of human osteoblast (MG63) cells. Hence, the optimized concentration of this compound from W. volubilis may used for treatment of bone related injuries externally.